2012
DOI: 10.2174/092986712801323225
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonyl Group-Containing Compounds in the Design of Potential Drugs for the Treatment of Diabetes and Its Complications

Abstract: Sulfonyl group-containing compounds constitute an important class of therapeutical agents in medicinal chemistry presumably because of the tense chemical structure and functionality of the sulfonyl, which could not only form hydrogen bonding interactions with active site residues of biological targets but also, as incorporated into core ring structure, constrain the side chains and allowed their specific conformations that fit the active sites. This review focuses on sulfonamides and sulfones, which cover more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 208 publications
0
71
0
1
Order By: Relevance
“…Previously this process has been used to construct high value C(sp 2 )−C(sp 3 ), and C(sp 2 )−N bonds through a low valent nickel mediator that was shown to be water sensitive . These results inspired the pursuit of a suite of reactions for the robust incorporation of medicinally relevant C−S and S−N bonds on‐DNA …”
Section: Figurementioning
confidence: 94%
“…Previously this process has been used to construct high value C(sp 2 )−C(sp 3 ), and C(sp 2 )−N bonds through a low valent nickel mediator that was shown to be water sensitive . These results inspired the pursuit of a suite of reactions for the robust incorporation of medicinally relevant C−S and S−N bonds on‐DNA …”
Section: Figurementioning
confidence: 94%
“…In recent years, a few reports suggested that certain kinds of chemical structures may relate to some corresponding cellular signaling pathways (5). Thus, we summarized the last five years' studies on TCM components functions on cancer cell signaling pathways and aimed at looking for association between chemical structure of TCM constituents and cancer cell signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In the same context, we believe that the sulfonyl group might impart the bioactivity of InhiTinib. In fact, sulfonyls are present in several established drugs known to antagonize multiple enzymes and receptors partaking in cellular processes such as metabolic regulation, angiogenesis, and tumor progression (Casini et al, 2002;Chen et al, 2012). Accordingly, InhiTinib may target: (i) the unfolded protein response by binding to heat shock factor 1 protein, (ii) the epigenome of cancer cells via histone methyltransferases modulation, and/or (iii) reduce antioxidant defenses by inhibiting thioredoxin reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using this HTS assay, we discovered a small compound, we named InhiTinib, exhibiting both immunomodulatory and anti-cancer properties. Although the involved molecular targets are still under investigation, InhiTinib's dual activity might originate from its sulfonyl group, which is a known bioactive entity affecting metabolic signaling pathways and present in several FDA-approved drugs (Chen et al, 2012;Piton et al, 2018). Indeed, InhiTinib's properties were herein elucidated in a series of in vitro and in vivo experiments which further test its safety and efficacy while highlighting its therapeutic potential.…”
Section: Introductionmentioning
confidence: 98%